Accurate estimation of large vessel length in growing children and adolescents for the purpose of pulse wave velocity calculation. - Witbooi, Lee-Roy Cecil (Stellenbosch : Stellenbosch University, 2018)
Thesis (MMed)--Stellenbosch University, 2018.